Pertimbangan Pembentukan Peraturan Perundang-Undangan Daerah Mengenai Pengelolaan Air Limbah Domestik Di Kabupaten Bengkalis - Arifin Bur; Wira Atma Hajri (UIR Law Review, 2018)
Environmental protection and management of domestic wastewater according to Article 63 Paragraphs (1), (2), and (3) of Law Number 32 Year 2009 shall be mandatory affairs related to basic services of regency / municipality governments, among them the provision of infrastructure and domestic waste water treatment facilities. Through the RPJMN 2015-2019 the government attempts, by 2019 every rural and urban Indonesian community already has access to proper sanitation facilities for domestic wastewater. In fact, the availability of domestic wastewater service to date is only 60.91% and not yet in Bengkalis Regency. This issue should not occur, because it will cause damage and / or environmental pollution. To respond to the needs of Bengkalis society it is treated a tool (tools) to regulate the management of domestic waste water in the form of local regulations. The result of the research shows that the consideration of the formulation of the regional regulation in Bengkalis Regency concerning the Management of Domestic Wastewater is philosophically the responsibility of the state and the government's duty to do so in order to realize the happiness of all Indonesian people and all mankind based on Pancasila and the Preamble of the 1945 Constitution. Juridical is based on the 1945 Constitution and other relevant legislation.